Lowering the Barriers to User Model Interoperability - WALSH, EDMOND; WADE, VINCENT PATRICK; WALSH, EDDIE (My University, 2009)
As people start to use many applications that require rich forms of user information, being able to share the contents of user models has become important. However, there are significant challenges in providing advanced levels of interoperability as user models are often very diverse in structure, syntax and semantics. This paper introduces FUMES; an approach to user model interoperability between heterogeneous educational applications. The aim of FUMES is to lower some of the common barriers to user model interoperability. It attempts to reduce the technical knowledge and domain expertise required from a human administrator of this process through the provision of domain-specific tools that include novel user model visualizations.
Ubiquitous User Modeling Workshop at the Conference on User Modeling, Adaptation, Personalization (UMAP)
PUBLISHED
Trento, Italy
Keywords: User Model, Interoperability, Exchange, Sharing, Semantics, Mapping, Visualization